2017
DOI: 10.7448/ias.20.5.21633
|View full text |Cite
|
Sign up to set email alerts
|

Expanding HIV testing and linkage to care in southwestern Uganda with community health extension workers

Abstract: Introduction: Achieving the UNAIDS goals of 90–90-90 will require more than doubling the number of people accessing HIV care in Uganda. Community-based programmes for entry into HIV care are effective strategies to expand access to HIV care, but few programmes have been evaluated with a particular focus on scale-up.Methods: Integrated Community Based Initiatives, a Uganda-based non-governmental organization, designed and implemented a programme of community-based HIV counselling and testing and facilitated lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
4
35
0
Order By: Relevance
“…For example, men are a particularly important group for tailored testing strategies, as they are less likely to be tested for HIV until they become ill . A number of models show promise for optimizing uptake of HIV testing and screening, including home‐ and community‐based testing, index partner testing, the integration of HIV testing into multi‐disease community‐level health campaigns, the use of lay cadres to expand testing and linkage to care, and self‐testing . Research approaches: Cluster randomized controlled trials (RCTs), rigorous programme evaluations, mixed methods studies on optimal timing of and barriers to repeat testing, and discrete choice experiments on preferences related to testing location (home or community based) and modalities (e.g. integration of HIV testing into other health services) will aid in identifying effective strategies that improve early diagnosis and linkage to care, particularly for underserved groups.…”
Section: Resultsmentioning
confidence: 99%
“…For example, men are a particularly important group for tailored testing strategies, as they are less likely to be tested for HIV until they become ill . A number of models show promise for optimizing uptake of HIV testing and screening, including home‐ and community‐based testing, index partner testing, the integration of HIV testing into multi‐disease community‐level health campaigns, the use of lay cadres to expand testing and linkage to care, and self‐testing . Research approaches: Cluster randomized controlled trials (RCTs), rigorous programme evaluations, mixed methods studies on optimal timing of and barriers to repeat testing, and discrete choice experiments on preferences related to testing location (home or community based) and modalities (e.g. integration of HIV testing into other health services) will aid in identifying effective strategies that improve early diagnosis and linkage to care, particularly for underserved groups.…”
Section: Resultsmentioning
confidence: 99%
“…Like our review, a recent consensus statement supporting safer conception and pregnancy for couples living with HIV found that access to SCS is limited by stigma toward HIV affected couples having children and that this stigma limits provision of safer conception services [75]. Increasing community education about SCSs via community health worker networks may help increase acceptability for previously unfamiliar conception strategies and reduce community-, provider-, or family-level stigma around pregnancy in HIV affected couples, as was accomplished with increasing community knowledge and acceptance of HIV testing [76, 77] and couples’ HIV counseling and testing [7880]. …”
Section: Discussionmentioning
confidence: 99%
“…The concept of differentiated care is applicable across the care cascade from prevention to testing to viral suppression. While the majority of studies in this issue are limited to the provision of ART, an article from Uganda by Asiimwe et al provides evidence that lay cadres can be leveraged to expand testing services and supporting linkage of PLHIV to care [ 50 ].…”
Section: Differentiated Care Across the Cascadementioning
confidence: 99%